ASM451: Records Management for Administrative Professionals / Faculty of Business Management - UiTM, Faculty of Business Management (2023)
This course describes the principles and procedures of managing records at the administrative level. The content includes the records management concepts, management of the active records, inactive records and the disposition of records.